LEGAL PROTECTION FOR CONSUMERS IN THE CASE OF EXCESS SPEED BOAT CAPACITY AT DUFA PORT – DUFA - fathurrahim Fathurrahim (Faculty of Law, Khairun University, 2022)
In a carriage agreement, the position of the parties, namely the carrier and the service user, is equal. As for the things that can cause harm to passengers due to the fault of the carrier, among others, accidents caused by the negligence of the captain, conditions of transportation that are not suitable for use, or due to lost or damaged passenger luggage. The government should increase the socialization activities of Law no. 17 of 2008, both to sea transportation operators and to the wider community as users of sea transportation services, so that legal protection efforts against sea transportation service users (passengers) as regulated in Law no. 17 of 2008 can actually be implemented by all sea transportation companies.